Câriye Kökenli Bir Selçuklu Hâtunu: Sultan Melikşah’ın Eşlerinden Tâceddîn Seferiyye Hâtun - Züriye ORUÇ (Gazi Akademik Bakış)
Taceddin Seferiyye Hatun is the ex-concubine wife of Sultan Melikshah and mother of Mohammad Tapar and Sencer, the last two rulers of the Great Seljuk Empire. Giving birth to Melikshah’s sons, she ascended to being an ummuveled, mother of children. This Seljuk lady of Kipchak origin rejoiced in seeing both her sons advance to the throne following the death of Sultan Berkyaruk and was one of the powerful women of the time. She had her own seat and treasure as the other wives of Melikshah. She also influenced the state affairs and possessed great esteem for her sons. She helped them get along well with each other through her advices and warnings, and she provided her grandson Mahmood b. Mohammad Tapar to be sent as the ruler of Iraq. Described as a generous and charitable lady, she built many charity foundations in Merv and Nishapur. Seferiyye Hatun died in the beginning of his son Sultan Sencer’s rule. There is no standalone study in the literature about this lady whom poet Muizzi composed eulogies talking about her religiousness and character. This study evaluates the information on Seferiyye Hatun in the sources.